The Effect of UHPFRC Material Coating As A Reinforcement Material Reinforced Concrete Column - Bakara, Ricky (Universitas Quality, 2025)
Damage to reinforced concrete structures, especially column structures, cannot be avoided. Therefore, reinforcing reinforced concrete structures is a must. The damage was caused by an earthquake and loads that exceeded the building's carrying capacity. To extend the service life of reinforced concrete structures, one of the methods used is to repair damaged structures. UHPFRC is a type of construction material that continues to develop and continues to be researched. In this study, there were 4 samples of reinforced concrete columns, one reinforced concrete column was designated as the control column and the other 3 reinforced concrete columns were tested with a load equal to 50% of the maximum load capacity of the control column. The damaged reinforced concrete columns were then reinforced with UHPFRC, with thickness variations of 10, 15 and 20 mm. Test results of reinforced concrete columns are described and analyzed graphically using the basic formula of reinforced concrete columns. The test results show that the maximum load obtained increases in all columns coated with UHPFRC. The increase in each column compared to the control column was 57.05%; and 269.54%. Also, reinforced concrete columns with layers of UPHFRC of different thicknesses are abbreviated with a CC-0 value of 11.62 mm; RCS-1 14.58mm; and the 20.59mm RCS-2. The increase in the maximum load obtained by each column shows that column repair with UHPFRC layers is possible as a reinforcement material for reinforced concrete columns in earthquake-prone areas.